LEGAL REVIEW OF ADULTERY CRIMES - Basri (MSJ : Majority Science Journal, 2024)
Adultery is a religious and legal prohibition against sexual intercourse between men and women without a legal marriage. It applies to individuals in religion, culture, and society. This research will discuss how the legal review of the criminal offense of adultery in Indonesia and how it is implemented in legal practice.The research method used is normative juridical legal research and approach through legislation.The results of this study explain that the criminal offense of adultery is regulated in the Criminal Code as a complaint offense. The legal review related to the criminal offense of adultery needs to clarify the practice of implementing the provisions in the Criminal Code against the perpetrators because it has not been able to provide a deterrent effect. In fact, the implementation of criminal regulations is not optimal due to the indifferent society towards norms, social values, and religion.